Support can increase use of the AUDIT‐C in Australian Aboriginal Community Controlled Health Services: a cluster randomized trial. (17th February 2021) - Conigrave, James H.; Harrison, Kristie H.; Lee, K. S. Kylie; Dobbins, Timothy A.; Hummerston, Beth; Hayman, Noel; Perry, Jimmy; Ivers, Rowena; Haber, Paul S.; Wilson, Scott; Johnson, David; Conigrave, Katherine M.
Abstract: Background and Aims: Unhealthy alcohol consumption is a key concern for Aboriginal and Torres Strait Islander ('Indigenous') communities. It is important to identify and treat at‐risk drinkers, to prevent harms to physical or social wellbeing. We aimed to test whether training and support for Aboriginal Community Controlled Health Service (ACCHS) staff would increase rates of alcohol screening and brief intervention. Design: Cluster randomized trial. Setting: Australia. Cases/Intervention/Measurements Twenty‐two ACCHSs that see at least 1000 clients per year and use Communicare as practice management software. The study included data on 70 419 clients, training, regular data feedback, collaborative support and funding for resources ($9000). Blinding was not used. The comparator was waiting‐list control (equal allocation). Alcohol Use Disorder Identification Test (AUDIT‐C) screening and records of brief interventions were extracted from practice management software at 2‐monthly intervals. Observations described the clinical actions taken for clients over each 2‐month interval. The baseline period (28 August 2016–28 August 2017) was compared with the post‐implementation period (29 August 2017–28 August 2018). We used multi‐level logistic regression to test the hypotheses that clients attending a service receiving active support would be more likely to be screened with AUDIT‐C (primary outcome) or to receive a brief intervention (secondary outcome). Findings: We observed an increase in the odds of screening with AUDIT‐C for both groups, but the increase was 5.52 [95% confidence interval (CI) = 4.31, 7.07] times larger at services receiving support. We found little evidence that the support programme increased the odds of a recorded brief intervention relative to control services (odds ratio = 2.06; 95% CI = 0.90, 4.69). Differences in baseline screening activity between treatment and control reduce the certainty of our findings. Conclusions: Providing Aboriginal Community Controlled Health Services with training and support can improve alcohol (AUDIT‐C) screening rates.